2016
DOI: 10.18227/1982-8470ragro.v9i4.2441
|View full text |Cite
|
Sign up to set email alerts
|

Composição florística e estrutura fitossociológica de um fragmento de Floresta Ombrófila Densa no município de Macaíba, RN

Abstract: Resumo: Estudos fitossociológicos em remanescentes florestais são de suma importância para caracterização da estrutura horizontal de comunidades florestais, pois gera dados que servem tanto de base para projetos de manejo florestal quanto para recuperação da biodiversidade. Nesse sentido, objetivou-se analisar a fitossociologia da vegetação, caracterizando a estrutura horizontal de um fragmento de Floresta Ombrófila Densa no Município de Macaíba-RN. Para a coleta de dados do componente arbóreo, utilizou-se a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
2
6
1
3
Order By: Relevance
“…As in the present study, other authors such as Araújo et al (2015), Colonetti et al (2009) and Costa Junior et al (2008) analyzing the phytosociological structure of fragments of Atlantic Forest also showed that a small number of species presented high density. According to Richards (1996), the dominance of a reduced number of species in the environment is a common occurrence in humid tropical forests.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As in the present study, other authors such as Araújo et al (2015), Colonetti et al (2009) and Costa Junior et al (2008) analyzing the phytosociological structure of fragments of Atlantic Forest also showed that a small number of species presented high density. According to Richards (1996), the dominance of a reduced number of species in the environment is a common occurrence in humid tropical forests.…”
Section: Discussionsupporting
confidence: 85%
“…The absolute dominance in the community was 11.75 m² ha -1 , being lower than that found by Costa Junior et al (2008), Araújo et al (2015) and Lima et al (2017) when analyzing the structure of Atlantic Forest fragments in the Brazilian Northeast, whose values were 22.13 m² ha -1 , 23.59 m² ha -1 and 19.63 m² ha -1 , respectively. This fact can be explained by the successional stage of the fragment of forest analyzed, the size of the area sampled, as well as the anthropic disturbances that preceded the incorporation of the fragment to the Conservation Unit Dois Irmãos State Park.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Esses estudos podem fornecer subsídios acerca das relações entre os indivíduos arbóreos e fatores ambientais. Araújo et al (2015) enfatizaram que a avaliação dos parâmetros fitossociológicos é importante pois permite caracterizar a estrutura horizontal das comunidades florestais, além de fazer inferências sobre a dinâmica das populações nos fragmentos, avaliando a importância ecológica das espécies, suas funções e as relações de interdependência entre os indivíduos, analisar a composição florística e a sua participação no processo de sucessão ecológica.…”
Section: Introductionunclassified
“…Em se tratando de sistemas agroflorestais, esses estudos podem fornecer subsídios sobre as relações entre os indivíduos arbóreos e fatores ambientais, gerando novos conhecimentos técnico-científicos, bem como as espécies arbóreas mais adequadas para cada região. Araújo et al (2015) enfatizaram que a avaliação dos parâmetros fitossociológicos são importantes, pois permite caracterizar a estrutura horizontal das comunidades florestais, fazer inferências sobre a dinâmica das populações nos fragmentos, avaliando a importância ecológica das espécies, suas funções e as relações de interdependência entre os indivíduos, além de analisar a composição florística e a sua participação no processo de sucessão ecológica.…”
Section: Introductionunclassified